Change of the Long-Term Nitrogen and Phosphorus in the Changjiang (Yangtze) River Estuary - Liu, Jing; Yao, Qingzhen; Mi, Tiezhu; Wei, Qinsheng; Chen, Hongtao; Yu, Zhigang (Frontiers in Marine Science, 2022)
The concentration and structure of nutrients play a key role in sustaining marine ecosystems. In recent decades, the change in nutrient input from land has led to significant changes in nutrient concentration and structure in the marginal sea and has had an important impact on the coastal ecosystem. Based on historical data from 1984 to 2016, the long-term variations in nutrients and their potential influencing factors, were analyzed in the Changjiang River Estuary. The concentration of dissolved inorganic nitrogen (DIN) increased gradually from 1984 to 2003, but after 2003 the concentration began to decrease. Compared with DIN, the change in dissolved inorganic phosphate (DIP) had a delayed effect and has exhibited a slow downward trend since 2005. The decreases in DIN and DIP are mainly due to the improvement of wastewater treatment efforts and chemical fertilizer use efficiency in recent years. The retention of nutrients by the Three Gorges Reservoir (TGR) has been another important factor since its completion in 2003, especially because the large amount of particulate phosphorus retained by the TGR has led to a significant decrease in the total phosphorus flux into the sea, which is the main reason for the decrease in DIP. The vatiations of DIP and DIN have been instrumental in causing the observed changes of phytoplankton community in the Changjiang River Estuary.